MULLA SADRA AND SUFISM (Fazlur Rahman Interpretation) - Nuruddin Al Akbar; Salih Abdulrahman Yousuf Assenhaji (Living Sufism: Journal of Sufism and Psychotherapy, 2024)
This article examines the complex link between Mulla Sadra, a famous person in Islamic philosophy, and Sufism, a mystical school within Islam, via the lens of Fazlur Rahman's perspective. The essay opens by describing the historical background in which Sadra formulated his theories, emphasizing the sociopolitical and religious issues of the time. Mulla Sadra's philosophy is distinguished by its emphasis on existence, knowledge, and the nature of reality, setting it distinct from Sufi thought. While Sufism frequently emphasizes experiential knowledge and mystical states, Sadra combines intellectual investigation with spiritual insight, resulting in a unique philosophical framework. This article examines the ontological, theological, and psychological aspects of Sadra’s ideas, contrasting them with Sufi perspectives. In the ontological domain, Sadra’s denial of existential monism calls into question the Sufi belief that actual existence is limited to God alone. The article investigates how Sadra's multi-tiered explanation of existence provides a more sophisticated perspective that accounts for multiple levels of reality. Theologically, Sadra’s intellectual approach to understanding the divine contrasts with Sufis' emphasis on mystical experience. Furthermore, the psychological part of Sadra's philosophy emphasizes the soul's active role in the search for knowledge, which differs from the more passive receiving of knowledge commonly found in Sufi teaching. By examining these characteristics, the article hopes to provide a thorough understanding of how Mulla Sadra's thought interacts with and differs from Sufi traditions. This article is basic research for scholars and students interested in the interconnections of philosophy and mysticism within Islam, providing insights into Mulla Sadra's thought's continued significance in modern discussions.